Underlying mechanism of surface (001) cubic ATiO3 (A = Pb, Sn) in enhancing thermoelectric performance of thin-film application using density functional theory - Mohammad Fariz Mohamad Taib (Tanjung Malim, 2021)
Underlying mechanism of surface (001) cubic ATiO3 (A = Pb, Sn) in enhancing thermoelectric performance of thin-film application using density functional theory by Mohammad Fariz Mohamad Taib